Book Review: Frank, Carolyn (1999) Ethnographic Eyes: A Teacher's Guide to Classroom Observation. Portsmouth, New Hampshire; Heinemann. - Cathy Compton-Lilly (Networks: An Online Journal for Teacher Research, 2001)
What might it mean for teachers to have "ethnographic eyes? Ethnography is generally defined as the study of culture. With teachers' eyes and attention focused on the cultures they encounter and help to create, teachers may find themselves learning about their students and rethinking their assumptions about teaching. Becoming an ethnographer provides teachers with an opportunity not only to learn the practices and procedures of teaching, but also to observe and make sense of their classroom observations and experiences.